Pioneer Axon Navigation Is Controlled by AEX-3, a Guanine Nucleotide Exchange Factor for RAB-3 in Caenorhabditis elegans. Issue 3 (1st July 2016) - Bhat, Jaffar M; Hutter, Harald
Abstract: Precise and accurate axon tract formation is an essential aspect of brain development. This is achieved by the migration of early outgrowing axons (pioneers) allowing later outgrowing axons (followers) to extend toward their targets in the embryo. In Caenorhabditis elegans the AVG neuron pioneers the right axon tract of the ventral nerve cord, the major longitudinal axon tract. AVG is essential for the guidance of follower axons and hence organization of the ventral nerve cord. In an enhancer screen for AVG axon guidance defects in a nid-1 /Nidogen mutant background, we isolated an allele of aex-3 . aex-3 mutant animals show highly penetrant AVG axon navigation defects. These defects are dependent on a mutation in nid-1 / Nidogen, a basement membrane component. Our data suggest that AEX-3 activates RAB-3 in the context of AVG axon navigation. aex-3 genetically acts together with known players of vesicular exocytosis: unc-64 /Syntaxin, unc-31 /CAPS, and ida-1 /IA-2. Furthermore our genetic interaction data suggest that AEX-3 and the UNC-6 /Netrin receptor UNC-5 act in the same pathway, suggesting AEX-3 might regulate the trafficking and/or insertion of UNC-5 at the growth cone to mediate the proper guidance of the AVG axon.